Experimental Performance Analysis for 2G/3G Cellular Networks based on Mobile Terminals - Jiménez-Licea, M.; Vidal-Beltrán, S.; López-Bonilla, J. (Journal of the Institute of Engineering, 2011)
This work presents the experimental results related to performance measurements in GSM, EDGE and WCDMA cellular data networks. Two Mobile Terminals were used, in order to take place the scenario. Power Level, Power vs Time, Modulation Analysis, Modulation Spectrum, (BER) Bit Error Rate and Throughput were considered in this analysis. Keywords: Component; GSM; EDGE; WCDMA; BER/BLER; Throughput DOI: http://dx.doi.org/10.3126/jie.v8i1-2.5094 Journal of the Institute of Engineering Vol. 8, No. 1&2, 2010/2011 Page : 25-38 Uploaded Date: 19 July, 2011